Comprehensive analysis of Sparassis crispa polysaccharide characteristics during the in vitro digestion and fermentation model. (April 2022) - Zhang, Wenyi; Hu, Bin; Liu, Chang; Hua, Hanyi; Guo, Yahui; Cheng, Yuliang; Yao, Weirong; Qian, He
Graphical abstract: Highlights: SCP-1 was indigestible in simulated saliva-gastrointestinal digestion. SCP-1 was utilized by gut microbiota to promote the production of short chain fatty acids. Beneficial genera, such as Prevotella 9, Dialister, Megamonas, and Megasphaera, were promoted by SCP-1 fermentation. SCP-1 significantly increased the carbohydrate, energy, and amino acid metabolism. Abstract: Sparassis crispa ( S.crispa ), an edible mushroom, is widely used as a natural medicine due to its excellent pharmacological activities, including antitumor, anti-angiogenic, and immunomodulatory activities. In the current study, the digestion and fermentation characteristics of an S.crispa polysaccharide (SCP-1) were investigated by the in vitro simulated models. Our results revealed that SCP-1 was not degraded during the simulated gastrointestinal tract. However, it was consumed by human intestinal microbiota, which was characterized by enhancing the production of short-chain fatty acids (such as acetate, propionate, and butyrate), and modifying the gut microbiota composition through promoting beneficial genera ( Prevotella 9, Dialister, Megamonas, and Megasphaera) and inhibiting proliferation of some harmful bacteria (i.e., Escherichia/Shigella). The PICRUSt prediction analysis indicated that SCP-1 significantly increased carbohydrate, energy, and amino acid metabolism. These results suggest that SCP-1 could be developed as a prebiotic addition and may improve host health by regulating gut microbiota.